Layered Oxide Cathodes Promoted by Structure Modulation Technology for Sodium‐Ion Batteries - Xiao, Yao; Abbasi, Nasir Mahmood; Zhu, Yan‐Fang; Li, Shi; Tan, Shuang‐Jie; Ling, Wei; Peng, Ling; Yang, Tingqiang; Wang, Lude; Guo, Xiao‐Dong; Yin, Ya‐Xia; Zhang, Han; et al. (Advanced functional materials, 2020)
Considering the ever‐growing climatic degeneration, sustainable and renewable energy sources are needed to be effectively integrated into the grid through large‐scale electrochemical energy storage and conversion (EESC) technologies. With regard to their competent benefit in cost and sustainable supply of resource, room‐temperature sodium‐ion batteries (SIBs) have shown great promise in EESC, triumphing over other battery systems on the market. As one of the most fascinating cathode materials due to the simple synthesis process, large specific capacity, and high ionic conductivity, Na‐based layered transition metal oxide cathodes commonly suffer from the sluggish kinetics, multiphase evolution, poor air stability, and insufficient comprehensive performance, restricting their commercialization application. Here, this review summarizes the recent advances in layered oxide cathode materials for SIBs through different optimal structure modulation technologies, with an emphasis placed on strategies to boost Na+ kinetics and reduce the irreversible phase transition as well as enhance the store stability. Meanwhile, a thorough and in‐depth systematical investigation of the structure–function–property relationship is also discussed, and the challenges as well as opportunities for practical application electrode materials are sketched. The insights brought forward in this review can be considered as a guide for SIBs in next‐generation EESC. The recent research progress of structure modulation technology on layered transition metal oxide cathodes for sodium‐ion batteries is summarized, concentrating especially on morphology design, coating technology, phase transition, ordering‐disordering, air stability, and composite structure to boost Na+ kinetics, suppress the irreversible phase transition, enhance the storage stability, improve the overall performance, and further realize sodium‐ion battery commercialization for market applications.